Disruption of NAP1 genes in Arabidopsis thaliana suppresses the fas1 mutant phenotype, enhances genome stability and changes chromatin compaction - Kolářová, Karolína; Nešpor Dadejová, Martina; Loja, Tomáš; Lochmanová, Gabriela; Sýkorová, Eva; Dvořáčková, Martina (The Plant journal, 2021)
Histone chaperones mediate the assembly and disassembly of nucleosomes and participate in essentially all DNA-dependent cellular processes. In Arabidopsis thaliana, loss-of-function of FAS1 or FAS2 subunits of the H3-H4 histone chaperone complex CHROMATIN ASSEMBLY FACTOR 1 (CAF-1) has a dramatic effect on plant morphology, growth and overall fitness. CAF-1 dysfunction can lead to altered chromatin compaction, systematic loss of repetitive elements or increased DNA damage, clearly demonstrating its severity. How chromatin composition is maintained without functional CAF-1 remains elusive. Here we show that disruption of the H2A-H2B histone chaperone NUCLEOSOME ASSEMBLY PROTEIN 1 (NAP1) suppresses the FAS1 loss-of-function phenotype. The quadruple mutant fas1 nap1;1 nap1;2 nap1;3 shows wild-type growth, decreased sensitivity to genotoxic stress and suppression of telomere and 45S rDNA loss. Chromatin of fas1 nap1;1 nap1;2 nap1;3 plants is less accessible to micrococcal nuclease and the nuclear H3.1 and H3.3 histone pools change compared to fas1. Consistently, association between NAP1 and H3 occurs in the cytoplasm and nucleus in vivo in protoplasts. Altogether we show that NAP1 proteins play an essential role in DNA repair in fas1, which is coupled to nucleosome assembly through modulation of H3 levels in the nucleus.
Keywords: histonové chaperony; Histone Chaperones; histone chaperones; Adenosine Triphosphatases; chromatin; mutace; adenosintrifosfatasy; Arabidopsis Proteins; Genomic Instability; Chromatin; Mutation; DNA repair; nestabilita genomu; histone variants; Arabidopsis; proteiny huseníčku